2018
DOI: 10.1002/pld3.94
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient sink limitation constrains growth in two barley species with contrasting growth strategies

Abstract: Mineral nutrients exert important limitations on plant growth. Growth is limited by the nutrient source when it is constrained by nutrient availability and uptake, which may simultaneously limit investment in photosynthetic proteins, leading to carbon source limitation. However, growth may also be limited by nutrient utilization in sink tissue. The relative importance of these processes is contested, with crop and vegetation models typically assuming source limitations of carbon and mineral nutrients (especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In the precision agriculture context, monitoring sink limitation in major crops may be used to inform the timing of fertiliser application to improve the balance between carbon and nitrogen resources in the plant (Basso et al, 2016; Maes & Steppe, 2019; Maresma, Ariza, Martínez, Lloveras, & Martínez‐Casasnovas, 2016). Both carbon and nitrogen can place limits on crop growth, development and yield (Burnett et al, 2016; Burnett, Rogers, Rees, & Osborne, 2018; White et al, 2016), and both source and sink limitations must be addressed for successful breeding of our future crops (Fernie et al, 2020; White et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the precision agriculture context, monitoring sink limitation in major crops may be used to inform the timing of fertiliser application to improve the balance between carbon and nitrogen resources in the plant (Basso et al, 2016; Maes & Steppe, 2019; Maresma, Ariza, Martínez, Lloveras, & Martínez‐Casasnovas, 2016). Both carbon and nitrogen can place limits on crop growth, development and yield (Burnett et al, 2016; Burnett, Rogers, Rees, & Osborne, 2018; White et al, 2016), and both source and sink limitations must be addressed for successful breeding of our future crops (Fernie et al, 2020; White et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Both carbon and nitrogen can place limits on crop growth, development and yield (Burnett et al, 2016;Burnett, Rogers, Rees, & Osborne, 2018;White et al, 2016), and both source and sink limitations must be addressed for successful breeding of our future crops (Fernie et al, 2020;White et al, 2016).…”
Section: Perspectives On Scaling Up Trait Detectionmentioning
confidence: 99%
“…An example of such an additional factor is a limited mineral nutrient supply [29,73]. The growth of sink tissues is highly sensitive to a shortage of mineral nutrients, especially nitrogen [74]. In terrestrial plants, the combination of elevated CO 2 and/or high light supply with low nitrogen supply exacerbates source-sink imbalance and downregulates the synthesis of photosynthetic protein [75,76], as well as other metabolic processes [61].…”
Section: Comparative Evaluation Of Plantmentioning
confidence: 99%
“…Burnett et al ( 2018 ) compared fast-growing domesticated annual barley with a slow-growing wild perennial relative under different levels of nutrient supply. They found that the perennial barley has a higher amino acid/sucrose ratio than the annual, implying a greater carbon source-limitation in the perennial than the annual barley.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the LAR-dependent growth in aCO 2 wheat, N supply levels above 0.3 g N kg −1 soil could no longer increase the leaf area with the saturated tiller number (Supplementary Figure 3), thus, exhibiting growth limitation by CO 2 rather than N as eCO 2 further increased the number of tillers and leaf area. Burnett et al (2018) compared fast-growing domesticated annual barley with a slow-growing wild perennial relative under different levels of nutrient supply. They found that the perennial barley has a higher amino acid/sucrose ratio than the annual, implying a greater carbon source-limitation in the perennial than the annual barley.…”
Section: Does the Dilution Effect Explain The Decrease In N Concentration In Plants?mentioning
confidence: 99%